Chronic hepatitis in a patient with rigid spine myopathy: Cause or just an association? - Hasan Özkan; Müyesser Arslan; Gökhan Kabacam; Adnan Tas; Gürsel Özgür; Gülşah Kaygusuz; Cemil Ekinci; Ayşe Serdaroğlu; Seyfettin Köklü (Turkish Journal of Gastroenterology, 2019)
-